Measurement of wave velocities and attenuation using an ultrasonic test system - Leong, Eng Choon (2011)
The use of ultrasonic testing to determine pulse velocities and small-strain elastic constants for rocks has been standardized in American Society for Testing and Materials (ASTM) standard D2845-95. However, the use of ultrasonic testing to determine pulse velocities and small-strain elastic constants of soils is less common, as soils have higher damping characteristics which result in measurement difficulty. The signal transmitted through soil is weak and very noisy. As a result, the signal must be properly processed to provide a reliable estimate of the wave travel time. In this paper, an ultrasonic test system consisting of compression and shear wave transducers, a pulser, and a data-acquisition system is evaluated for measurement of both compression and shear wave velocities. Among the specimens tested were fully saturated and unsaturated soil specimens. The effects of acoustic coupling and signal processing on the transmitted pulse were investigated. The strain levels associated with the determination of the wave velocities were also measured. Furthermore, a method for determining attenuation characteristics for soil specimens from the frequency spectra is suggested.